Lived experiences of couples in a relationship where one partner is diagnosed with a mental illness - Mokoena, Andile G. (Curationis, 2019)
BACKGROUND: A partner with mental illness can be challenging in a couple’s relationship. Mental illness brings about disintegration in the relationship because the partner without mental illness takes on more responsibilities than before. The partner without mental illness can be subjected to multiple risks, including stress and burden of care. The lived experiences of couples in a relationship where one partner is diagnosed with a mental illness is an under-researched area of mental health. OBJECTIVES: To explore and describe the lived experiences of couples in a relationship where one partner is diagnosed with a mental illness. METHOD: A qualitative, descriptive, exploratory and contextual research design was utilised. A purposive sampling method was used to sample participants for this study. Five couples, where one partner was diagnosed with a mental illness, participated in the study. Ten in-depth, individual, phenomenological interviews were conducted to provide rich descriptions of the couples’ experiences. Data were analysed using thematic analysis. An independent coder assisted with the data analysis. A consensus discussion was held between the independent coder and the interviewing researcher to agree on the identified themes. RESULTS: Four themes with categories emerged from the data analysis: couples experienced changed social roles in their relationship, emotional upheaval was experienced by the individual partners in the couple relationship, interpersonal distance was experienced in the couple’s relationship and a changed relationship with the self was experienced by the individual partners in the couple relationship. CONCLUSION: The results concluded that couples experienced that the presence of mental illness in their relationship adversely affects the relationship, thus emphasising the need to empower the couples dealing with challenges of being in a relationship where one partner is diagnosed with a mental illness.